Potential role of proteasome on c-jun related signaling in hypercholesterolemia induced atherosclerosis - SÖZEN, AHMET ERDİ; YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE BV, 2014)
Atherosclerosis and its complications are major causes of death all over the world. One of the major risks of atherosclerosis is hypercholesterolemia. During atherosclerosis, oxidized low density lipoprotein (oxLDL) regulates CD36-mediated activation of c-jun amino terminal kinase-1 (JNK1) and modulates matrix metalloproteinase (MMP) induction which stimulates inflammation with an invasion of monocytes. Additionally, inhibition of proteasome leads to an accumulation of c-jun and phosphorylated c-jun and activation of activator protein-1 (AP-1) related increase of MMP expression. We have previously reported a significant increase in cluster of differentiation 36 (CD36) mRNA levels in hypercholesterolemic rabbits and shown that vitamin E treatment prevented the cholesterol induced increase in CD36 mRNA expression. In the present study, our aim is to identify the signaling molecules/transcription factors involved in the progression of atherosclerosis following CD36 activation in an in vivo model of hypercholesterolemic (induced by 2% cholesterol containing diet) rabbits. In this direction, proteasomal activities by fluorometry and c-jun, phospo c-jun, JNK1, MMP-9 expressions by quantitative RT-PCR and immunoblotting were tested in aortic tissues. The effects of vitamin E on these changes were also investigated in this model. As a result, c-jun was phosphorylated following decreased proteasomal degradation in hypercholesterolemic group. MMP-9 expression was also increased in cholesterol group rabbits contributing to the development of atherosclerosis. In addition, vitamin E showed its effect by decreasing MMP-9 levels and phosphorylation of c-jun. (C) 2014 The Authors. Published by Elsevier B.V.
Keywords: Atherosclerosis; Hypercholesterolemia; Proteasome; JNK1; AP-1; Vitamin E; SMOOTH-MUSCLE-CELLS; SCAVENGER RECEPTOR EXPRESSION; ACTIVATED PROTEIN-KINASES; VITAMIN-E; OXIDIZED LDL; OXIDATIVE STRESS; TRANSCRIPTION FACTOR; MAP KINASES; IN-VITRO; RABBITS